ANALISIS PERBEDAAN IKLIM MIKRO TERHADAP KENYAMANAN PENGUNJUNG PADA RUANG TERBUKA HIJAU DI KOTA PEKANBARU - Miranti Putri Ridwan Gucci; Zulkarnaini Zulkarnaini; Sofia Anita (Program Pascasarjana Universitas Riau, 2016)
The aim of this study was to analyze differences in microclimate, the comfort index and the perception of comfort of visitors in each of the green open space. Location of the study are in three different green open space that is City Forest, City Park and Polytechnic Caltex Riau Park (PCR). The method used was a survey and observation. The sampling method is purposive sampling. The result showed that the average temperature of City forest reached 27.35ºC with 72.12% an average of humidity and 9274.67 Lux intensity of light. Furthermore, comfort index in the city forest was uncomfortable and perception comfort of visitors in good categories the day while, the lack of good are in the afternoon. The average temperature of the city park was 27.83ºC with 71.55% an average of humidity and at 6239.33 Lux intensity of light. Comfort index in the city park was also in the category of comfortable and perceived the comfort of visitors in the category of being there during the day and poor in the afternoon. The average temperature, humidity, intensity of light in the PCR Park were, 30.61ºC, 64.30%, and 16567.67 Lux, respectively. The comfort index in PCR Park was uncomfortable. Nevertheless, the perception of visitors comfort was better in the morning and poor during the day.